Exploring The Influence Of Entrepreneurial Abilities On Graduates' Risk-Taking Readiness - OGBARI, Mercy Ejovwokeoghene (Journal of Entrepreneurial and Business Diversity, 2023)
Purpose:Most graduates from Nigerian universities are trained to rely on white-collar employment for their living rather than being given entrepreneurial or self-reliant skills. Because of this, a sizeable percentage of Nigerian university graduates are still looking for rewarding jobs today. Although they theoretically understand becoming self-sufficient, they need more business acumen. It is, therefore, vital to equip these graduates with the abilities and information required to enable them to create employment rather than seek it. As a result, this study looked into the impact of entrepreneurial abilities on graduates' readiness to venture and accept risks.Methodology:The study's research tool was a thoughtfully created questionnaire with a descriptive design. The researcher employed both a descriptive study design and a causal research design. The population of the study consisted of 7,098 Covenant University graduates. The Yamane formula was used to determine the sample size for this investigation, which was 379. The study's random sample techniques were practical, clear-cut, and intended.Findings:The study's conclusions show a significant and favorable relationship between graduates' risk-taking propensity and entrepreneurial skills among Nigerian university students.Implication:The study finds that graduates' tendency to take risks and their intention to start their businesses are highly influenced by entrepreneurial education and the development of entrepreneurial skills through self-learning and taught courses.